2022
DOI: 10.3389/fpsyt.2022.841429
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plasma Homocysteine Level on the Risk of Three Major Psychiatric Disorders: A Mendelian Randomization Study

Abstract: BackgroundHigher homocysteine (Hcy) level has been suggested to be associated with major psychiatric disorders (MPDs), such as schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD). We investigated the causal relationships between plasma Hcy level and MPDs risks using the Mendelian randomization (MR) method.MethodsWe selected 18 loci associated with plasma Hcy level from a large-scale genome-wide association study (GWAS) as genetic instruments. Genetic associations with SCZ, MDD, BD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…These studies partially explain the mechanisms involved in Hcy abnormalities leading to schizophrenia. A Mendelian randomization study reported that increased plasma Hcy levels increased the risk of schizophrenia and bipolar disorders [ 12 ]. A systematic review and meta-analysis reported that levels of Hcy were higher in first-episode psychosis compared to controls, suggesting that an imbalance of antioxidant status may be relevant to first-episode psychosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies partially explain the mechanisms involved in Hcy abnormalities leading to schizophrenia. A Mendelian randomization study reported that increased plasma Hcy levels increased the risk of schizophrenia and bipolar disorders [ 12 ]. A systematic review and meta-analysis reported that levels of Hcy were higher in first-episode psychosis compared to controls, suggesting that an imbalance of antioxidant status may be relevant to first-episode psychosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no causal relationship was found between plasma Hcy levels and the risk of MDD and BD-II. 31 Nevertheless, there are several limitations of the MR study that need to be considered carefully. For example, the number of genetic instruments used in the MR analysis was limited, and the risk of BD may be affected by exposure to higher Hcy levels at a particular time, whereas their MR analysis investigated lifelong elevated Hcy levels in BD.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of 5 μmol/L in homocysteinemia appears to correspond to a 70% (OR 1.7) inflation of the risk of schizophrenia ( 14 ). A Mendelian randomisation study also showed that elevated plasma homocysteine levels could increase the risk of schizophrenia ( 15 ). Folate deficiency and hyperhomocysteinemia appears to be more specifically associated with negative symptoms and cognitive alterations in this population ( 16 ).…”
Section: Introductionmentioning
confidence: 99%